PEMANFAATAN ABU SEKAM PADI DAN PLASTIK PET MENJADIPENGGANTI SEBAGIAN AGREGAT HALUS DALAM PEMBUATAN PAVING BLOCK (Menara: Jurnal Teknik Sipil, 2022)
This Research aims to utilize waste rice husk ash and PET plastic, in the manufacture of Paving block, Because PET plastic waste has the advantages of not easy to decompose and durable while rice husk ash has the advantage of good binding power, where PET plastic waste does not have the binding power to bind other mixtures, then to cover this deficiency, rice husk ash in combined with PET plastic. The method use in this research is ecxperimental method on paving block by replacing some of the fine aggregate with artificial aggregate with variations 0%, 5%, 10% dan 15% of the weight of the fine aggregate. The test object size is 210 mm x 105 mm x 60 mm. Thpes of the test carried out are visible and sizing test, compressive strength test, wear resistance test dan water absorption test. Testing the compressive strength values ​​for variations of 5%, 10% and 15% respectively are 20 MPa, 17.597 MPa, and 15.927 MPa. Paving blocks with a variation of 5% are included in the B quality, while the paving blocks with a variation of 10% & 15% are not included in the B quality but into the C quality.